Status Of Skills Development In The Financial Sector (A Namibia Case Study) - Muyoba, Heritha Nankole (Organisational Psychology, 2020)
A financial sector establishes stability on the capabilities and skills of its human resources, which comprises the essential material for its growth. Therefore, it is essential that the financial service sector improves the quality of its human resources in order to ensure enough human capital that fosters ongoing growth. The Namibian Government identified the shortage of skills in the financial sector as one of the biggest obstacles in realising economic growth targets set out in Namibia’s Vision 2030. Namibia suffers from a shortage of skills in the areas of auditing, actuarial science, chartered accountancy, information technology, investment banking, property evaluation, and compliance and risk management. The objectives of the study were to investigate the nature of strategies implemented in the financial service sector in order to address skills shortages experienced by this industry, to examine development challenges encountered by the financial sector, to identify critical and scarce skills within the financial industry and to investigate skills development funding mechanisms currently utilised by employers in the financial sector in Namibia. The study aimed to document the status of skills in the financial sector since the inception of the Namibian Financial Sector Strategy and Charter in 2012 Stratified sampling was used to select a sample from the 174 institutions classified as the study population. The banking and non-banking entities sampled were categorised according to characteristics they had in common which would identify them as homogeneous. Therefore, participants were divided into sub-sector categories. The database built from surveying those institutions was stratified according to the characteristics. The research instruments were two questionnaires, one for employers and the other for universities, which were utilised to collect data. The essential finding of the research maintains that skills shortages, the expenditure budget allocated for training and the overall labour turnover in the financial sector hinders its skills development. A discussion of the study’s findings was presented and concluded with recommendations for future research. The shortage of skills and a lack of experience in the workplace, coupled with labour turnover, were identified as challenges experienced by the industry. What is evident from the study is that these challenges are not unique to Namibia but affect the global labour marketplace as well. The situation could, in part, be due to the process of globalisation.